Developing Progressive Islamic Aqidah Teaching Materials for Middle School Students - Romadlon, Dzulfikar Akbar; Istikomah, Istikomah; Haryanto, Budi (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This research will develop teaching materials for aqidah from the perspective of the "Progressive Islam" concept initiated by Muhammadiyah. This study used the Research and Development (R&D) method using ADDIE (Analyze, Design, Develop, Implement, Evaluation) model to develop teaching materials aqidah from a progressive Islamic perspective for junior high school students. The population in this study were class VII students of SMP Muhammadiyah 9 Sidoarjo. The sampling technique used was non-probability sampling with purposive sampling. Qualitative data is obtained through observation, written responses, and suggestions, while quantitative data is obtained from tests. The research results showed that the validity of the aqidah was 86.36%, material expert 84.25%, and Islamic religious education 84.42% in the valid category. For effectiveness, data sources were obtained from student learning outcomes before and after using progressive Islamic teaching materials. The pre-test results obtained an average of 77.65, and during the post-test, it increased to 80.7. The results of this research and development suggest that the use of progressive Islamic teaching materials in teaching aqidah class VII students at SMP Muhammadiyah 9 Sidoarjo is appropriate.